Postpartum problems related only to breastfeeding the baby - Linda Puji Astutik; Yena wineini Migang (Science Midwifery, 2025)
According to the WHO, exclusive breastfeeding is giving only breast milk to an infant from birth until 6 months of age, without any other food or drink, except for medications, vitamins, or minerals in syrup form prescribed by a doctor. Breastfeeding should ideally begin within the first hour after birth and be exclusive for the first six months for optimal growth, development, and health. Exclusive breastfeeding for infants aged 0-42 days is not without postpartum issues experienced by mothers. Therefore, this study aims to determine the relationship between postpartum problems in mothers and exclusive breastfeeding in infants. This is an analytical research type with a cross-sectional design. The sample size is 114 people, selected using the total sampling technique. From the research findings, it was discovered that the majority of mothers who did not experience postpartum problems tended to breastfeed their babies exclusively. There is a significant relationship between postpartum problems and exclusive breastfeeding (p-value = 0.026). Therefore, to support exclusive breastfeeding, midwives must help mothers overcome postpartum problems and be active in preventing problems during the puerperium.